Chronic intracortical neural recordings using microelectrode arrays coated with PEDOT–TFB. (1st March 2016) - Charkhkar, Hamid; Knaack, Gretchen L.; McHail, Daniel G.; Mandal, Himadri S.; Peixoto, Nathalia; Rubinson, Judith F.; Dumas, Theodore C.; Pancrazio, Joseph J.
Graphical abstract: Abstract: Microelectrode arrays have been extensively utilized to record extracellular neuronal activity for brain–machine interface applications. Modifying the microelectrodes with conductive polymers such as poly(3, 4-ethylenedioxythiophene) (PEDOT) has been reported to be advantageous because it increases the effective surface area of the microelectrodes, thereby decreasing impedance and enhancing charge transfer capacity. However, the long term stability and integrity of such coatings for chronic recordings remains unclear. Previously, our group has demonstrated that use of the smaller counter ion tetrafluoroborate (TFB) during electrodeposition increased the stability of the PEDOT coatings in vitro compared to the commonly used counter ion poly(styrenesulfonate) (PSS). In the current work, we examined the long-term in vivo performance of PEDOT–TFB coated microelectrodes. To do so, we selectively modified half of the microelectrodes on NeuroNexus single shank probes with PEDOT–TFB while the other half of the microelectrodes were modified with gold as a control. The modified probes were then implanted into the primary motor cortex of rats. Single unit recordings were observed on both PEDOT–TFB and gold control microelectrodes for more than 12 weeks. Compared to the gold-coated microelectrodes, the PEDOT–TFB coated microelectrodes exhibited an overall significantly lower impedance and higher number of units per microelectrode specifically for the first four weeks. The majority of PEDOT–TFB microelectrodes with activity had an impedance magnitude lower than 400 kΩ at 1 kHz. Our equivalent circuit modeling of the impedance data suggests stability in the polymer-related parameters for the duration of the study. In addition, when comparing PEDOT–TFB microelectrodes with and without long-term activity, we observed a distinction in certain circuit parameters for these microelectrodes derived from equivalent circuit modeling prior to implantation. This observation may prove useful in qualifying PEDOT–TFB microelectrodes with a greater likelihood of registering long-term activity. Overall, our findings confirm that PEDOT–TFB is a chronically stable coating for microelectrodes to enable neural recording. Statement of significance: Microelectrode arrays have been extensively utilized to record extracellular neuronal activity for brain–machine interface applications. Poly(3, 4-ethylenedioxythiophene) (PEDOT) has gained interest because of its unique electrochemical characteristics and its excellent intrinsic electrical conductivity. However, the long-term stability of the PEDOT film, especially for chronic neural applications, is unclear. In this manuscript, we report for the first time the use of highly stable PEDOT doped with tetrafluoroborate (TFB) for long-term neural recordings. We show that PEDOT–TFB coated microelectrodes on average register more units compared to control gold microelectrodes for at least first four weeks post implantation. We collected the in vivo impedance data over a wide frequency spectrum and developed an equivalent circuit model which helped us determine certain parameters to distinguish between PEDOT–TFB microelectrodes with and without long-term activity. Our findings suggest that PEDOT–TFB is a chronically stable coating for neural recording microelectrodes. As such, PEDOT–TFB could facilitate chronic recordings with ultra-small and high-density neural arrays.